Do Alcohol Relapse Episodes During Treatment Predict Long‐Term Outcomes? Investigating the Validity of Existing Definitions of Alcohol Use Disorder Relapse. (3rd September 2016) - Maisto, Stephen A.; Roos, Corey R.; Hallgren, Kevin A.; Moskal, Dezarie; Wilson, Adam D.; Witkiewitz, Katie
Abstract : Background: The construct of relapse is used widely in clinical research and practice of alcohol use disorder (AUD) treatment. The purpose of this study was to test the predictive validity of commonly appearing definitions of AUD relapse in the empirical literature. Methods: Secondary analyses of data from Project MATCH and COMBINE were conducted using 7 definitions of "relapse" based on drinking quantity within a single drinking episode: any drinking; at least 4/5 drinks for women/men; at least 4.3/7.1 drinks for women/men; at least 6/7 drinks for women/men; at least 6 drinks; at least 7/9 drinks for women/men; and at least 8/10 drinks for women/men. Relapse was used to predict alcohol consumption, related consequences, and nonconsumption outcomes (quality of life, psychosocial functioning) at the end of treatment and up to 1 year posttreatment. Results: Regression analyses indicated within‐treatment relapse definitions significantly predicted end‐of‐treatment alcohol consumption and alcohol‐related consequences. Heavy drinking definitions were generally more predictive than the any drinking definition, but no single heavy drinking definition was consistently a better predictor of outcomes. Relapse definitions were less predictive of longer‐term alcohol‐related outcomes and both shorter‐ and longer‐term nonconsumption outcomes, including health and psychosocial functioning. Conclusions: One particular definition of relapse did not consistently stand out as the best predictor. Advances in AUD research may require reconceptualization of relapse as a multifaceted dynamic process and may consider a wider range of relevant behaviors (e.g., health and psychosocial functioning) when examining the change process in individuals with AUD. Abstract : This study tested the power of seven definitions of during‐treatment "relapse" based on drinking quantity within a single drinking episode to predict alcohol use and psychosocial end of treatment and 12‐month post‐treatment outcomes. Secondary analyses of data from Projects MATCH and COMBINE were conducted. No definition of relapse stood out as the best predictor. Advances in AUD research may require reconceptualization of relapse as a multifaceted dynamic process when examining AUD clinical course.